ABOUT THE ROLE AND FUNCTION OF ART IN PEOPLE'S LIVES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article is written about the role and activity of art in people's lives. Further improvement of the cultural service, ensuring the enjoyment of the artistic wealth of our people is aimed at supporting and encouraging the spirit of art.